2016
DOI: 10.1021/acs.jced.6b00608
|View full text |Cite
|
Sign up to set email alerts
|

Excess Molar Enthalpies of Deep Eutectic Solvents (DESs) Composed of Quaternary Ammonium Salts and Glycerol or Ethylene Glycol

Abstract: Molar enthalpies of mixing (H E) were measured for the following deep eutectic solvents (DESs): {choline chloride + glycerol}, {choline chloride + ethylene glycol}, {tetrabutylammonium chloride + glycerol}, and {tetrabutylammonium chloride + ethylene glycol} at 323.15 K and molar ratios of 1:4, 1:3, 1:2 and 1:1. Results show that all systems are endothermic, with H E values ranging from 1.90 to 5.35 kJ·mol–1. Results indicate that the intermolecular interactions between the molecules of the pure components are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 34 publications
4
40
0
Order By: Relevance
“…In that work it was observed that the interactions with the chloride anion seem to be favored by some sugar configurations, as demonstrated by the difference in the values of the activity coefficient between the two isomers reported there, arabinose and xylose. 34 16 Although the systems studied are often reported as DES, 4,5,12,13,16,[35][36][37][38] it is here demonstrated that in some mixtures the eutectic temperature is very close to that predicted assuming ideality ([Ch]Cl+ethylene glycol or propanediol). The absence of favourable interactions on these systems is further supported by the excess enthalpy measurements reported by Lopez-Porfiri et al 37 showing these mixtures to be endothermic.…”
Section: Solid-liquid Phase Diagramsmentioning
confidence: 54%
“…In that work it was observed that the interactions with the chloride anion seem to be favored by some sugar configurations, as demonstrated by the difference in the values of the activity coefficient between the two isomers reported there, arabinose and xylose. 34 16 Although the systems studied are often reported as DES, 4,5,12,13,16,[35][36][37][38] it is here demonstrated that in some mixtures the eutectic temperature is very close to that predicted assuming ideality ([Ch]Cl+ethylene glycol or propanediol). The absence of favourable interactions on these systems is further supported by the excess enthalpy measurements reported by Lopez-Porfiri et al 37 showing these mixtures to be endothermic.…”
Section: Solid-liquid Phase Diagramsmentioning
confidence: 54%
“…Choline chloride (>99%) and ethylene glycol (anhydrous, 99.8%) were purchased from Sigma-Aldrich. Two DES were prepared by weighting and adding ethylene glycol and choline chloride in a molar ratio of 2:1 and 3:1, which is in the region of maximum freezing depression [20,21].The DES were mixed by mechanical agitation at about 60°C for 30 min until a clear homogeneous liquid phase was obtained and served as stock solutions. Two series of 10 working solutions were prepared by pipetting and addition of deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…All the DES used in this work have a higher density than the pure HBD used in their preparation and at a fixed temperature, the density increases with a higher molar fraction of the HBA. Other workers 45,46 have shown that the DES in general exhibit a non ideal behavior. For the systems studied in this work we cannot confirm this finding as the density of solid choline chloride has not been reported in literature and the first derivative of molar volume remains constant over the limited range of mole fractions studied.…”
Section: Density and Viscosity Measurementsmentioning
confidence: 96%